Differences In Geography Learning Results Using The Nearpod Application on The Material Diversity of Flora Fauna in Indonesia Class XI Academic Year 2023/2024 SMA Negeri 21 Surabaya - Rully Ardiansyah; Aisy, Izdihar; Tria Lestari; Sri Murtini; Sukma Perdana Prasetya (Universitas Negeri Surabaya, 2025)
Instructional media is a device that allows students to acquire information , knowledge , experience, and skill in teaching and learning process. The problem often faced by teachers in teaching is to choose appropriate instructional media in the learning process so that students fully understand the given subject. This study aimed to determine differences in cognitive learning outcomes of students after using gradual and thorough Nearpod application instructional media based on cognitive load theory to subject diversity of flora and fauna in Indonesia. This research is a quasi experimental factorial design with 2 × 1. Source of this study come from students , media specialists , and expert material obtained from the research questionnaire. Meanwhile learning outcomes data that is obtained through a pre-test and post-test .The results based on the score of the student post-test shows that class which use the Nearpod application media had an average value of 90, better than class that use no instructional media which scored 74 so there is significant differences occurred between the three classesis evidenced in the results of the Independent T Test results that have a Sig. 0,031 this suggests there is a difference , then H0 is rejected and H1 accepted . In other words, Nearpod application media influenced on student learning outcomes . Based on this study it is suggested that the teacher can use a Nearpod application instructional media in teaching process